Spatial variation in the effects of size and age on reproductive dynamics of common coral trout Plectropomus leopardus. Issue 4 (18th March 2014) - Carter, A. B.; Russ, G. R.; Tobin, A. J.; Williams, A. J.; Davies, C. R.; Mapstone, B. D.
<x xml:space="preserve">Abstract</x> The effects of size and age on reproductive dynamics of common coral trout Plectropomus leopardus populations were compared between coral reefs open or closed (no‐take marine reserves) to fishing and among four geographic regions of the Great Barrier Reef (GBR), Australia. The specific reproductive metrics investigated were the sex ratio, the proportion of vitellogenic females and the spawning fraction of local populations. Sex ratios became increasingly male biased with length and age, as expected for a protogyne, but were more male biased in southern regions of the GBR (Mackay and Storm Cay) than in northern regions (Lizard Island and Townsville) across all lengths and ages. The proportion of vitellogenic females also increased with length and age. Female P. leopardus were capable of daily spawning during the spawning season, but on average spawned every 4·3 days. Mature females spawned most frequently on Townsville reserve reefs (every 2·3 days) and Lizard Island fished reefs (every 3·2 days). Females on Mackay reefs open to fishing showed no evidence of spawning over 4 years of sampling, while females on reserve reefs spawned only once every 2–3 months. No effect of length on spawning frequency was detected. Spawning frequency increased with age on Lizard Island fished reefs, declined with age on Storm Cay fished reefs, and declined with age on reserve reefs in all regions. It is hypothesized that the variation in P. leopardus sex ratios and spawning frequency among GBR regions is primarily driven by water temperature, while no‐take management zones influence spawning frequency depending on the region in which the reserve is located. Male bias and lack of spawning activity on southern GBR, where densities of adult P. leopardus are highest, suggest that recruits may be supplied from central or northern GBR. Significant regional variation in reproductive traits suggests that a regional approach to management of P. leopardus is appropriate and highlights the need for considering spatial variation in reproduction where reserves are used as fishery or conservation management tools.